Assessment of Social Returns for Sustainability of Ban Du Silk Handicraft Community Enterprise - Singyam, Pornsawad; Wirotthitiyawong, Nilubon; Thongchan, Sunisa; Khunardsungnern, Duangporn; Jiracheewee, Jiraporn (Research Community and Social Development Journal, 2024)
Background and Objective: This research encourages to foster the sustainable development of community enterprises, focusing on financial stability, social cohesion, and promoting appropriate enduring opportunities. The objective of this study were to: 1) study the operational status and evaluate operational performance, 2) develop a business management model to enhance guidelines for value creation, and 3) evaluate the social return on investment, with research scope focusing on the community enterprise of the Ban Du silk handicreaft. Methology: The research methodology employs a mixed-method approach, the study targets three qualitative sample groups through purposive sampling, including 13 operational staffs, 5 community members, and 5 support personnel. Ethically approved semi-structured interviews were conducted, complemented by individual interviews, non-participatory observation, focus group discussions, and document analysis. Data analysis techniques encompassed content analysis, the Five Force Model, PEST Analysis, SWOT Analysis, Business Model Canvas (BMC), Logical Model Analysis, and Social Return on Investment (SROI) analysis. Results: In summary, the results of this study showed that: 1) The Ban Doo silk handicraft community, adorned with the royal emblem "Blue Peacock," operates through a nine-step production process, markets high-value products, and caters to a specialized customer base. 2) The industry faces intense competition with numerous new entrants and abundant substitute products, empowering customers with price negotiation leverage and wider product options. Traditional offline and online distribution channels persist for sellers. Environmental analysis revealed 7 strengths, 4 weaknesses, 6 opportunities, and 9 obstacles, forming the basis for a comprehensive business management model focusing on value creation across 9 dimensions: partnerships, key resources, key activities, value proposition, customer relationships, key resources, distribution channels, overall business costs, and primary revenue streams. 3) Development initiatives based on the business management model in 2022 yielded tangible investment returns and social benefits. Discussion: The Social Return on Investment (SROI) assessment emerges as a pivotal tool for comprehending the multifaceted impacts of community enterprise activities, transcending mere financial metrics to encompass broader societal outcomes. Suggestion: The Social Return on Investment (SROI) continuous feedback mechanisms and iterative improvement processes are essential for refining social return on investment assessments and ensuring ongoing enhancement.